Healthcare costs in patients with advanced non-small cell lung cancer and disease progression during targeted therapy: a real-world observational study. (1st February 2018) - Skinner, Karen E.; Fernandes, Ancilla W.; Walker, Mark S.; Pavilack, Melissa; VanderWalde, Ari
Abstract: Aims: To assess healthcare costs during treatment with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) and following disease progression in patients with advanced non-small cell lung cancer (NSCLC). Methods: A retrospective analysis of medical records of US community oncology practices was conducted. Eligible patients had advanced NSCLC (stage IIIB/IV) diagnosed between January 1, 2008 and January 1, 2015, initiated treatment with erlotinib or afatinib (first-line or second-line), and had disease progression. Monthly Medicare-paid costs were evaluated during the TKI therapy period and following progression. Results: The study included 364 patients. The total mean monthly cost during TKI therapy was 20, 106 (95% confidence interval [CI] = 16, 836–23, 376), of which 47.0% and 42.4% represented hospitalization costs and anti-cancer therapy costs, respectively. Following progression on TKI therapy (data available for 316 patients), total mean monthly cost was 19, 274 (95% CI = 15, 329–23, 218), and was higher in the 76.3% of patients who received anti-cancer therapy following progression than in the 23.7% of those who did not (20, 490 vs 15, 364; p < .001). Among patients who received it, anti-cancer therapy (11, 198; 95% CI = 7, 102–15, 295) represented 54.7% of total mean monthly cost. Among patients who did not receive anti-cancer therapy, hospitalization (13, 829; 95% CI = 4, 922–22, 736) represented 90.0% of total mean monthly cost. Impaired performance status and brain metastases were significant predictors of increased cost during TKI therapy. Limitations: The study design may limit the generalizability of findings. Conclusions: Healthcare costs during TKI treatment and following progression appeared to be similar and were largely attributed to hospitalization and anti-cancer therapy. Notably, almost one-quarter of patients did not receive anti-cancer therapy following progression, potentially indicating an unmet need; hospitalization was the largest cost contributor for these patients. Additional effective targeted therapies are needed that could prolong progression-free survival, leading to fewer hospitalizations for EGFR mutation-positive patients.